Pension Liabilities of the Central Government: Projections and Implications - Planning Commission (Planning Commission Government of India, 2004)
The report on Pension Liabilities of the Central Government provides a data-driven analysis of the sustainability of India’s pension system. Examining historical trends and projecting future liabilities, it finds that pension and salary expenditures account for approximately 9.2% of GDP, with growth in liabilities expected at a manageable 8.1% annually under the current defined-benefit framework. Key drivers of pension growth include the number of pensioners, average pensions, dearness relief, and inflation-indexed components, which constitute 61–75% of total expenditures. The study highlights that while reforms toward defined-contribution schemes may be considered for new employees, the existing system is largely sustainable, provided administrative efficiency is maintained. Complementing this analysis, working papers on India’s economic situation explore external economic vulnerabilities, poverty, health, population growth, fiscal measures, and debt market development, emphasizing the need for responsive policies to ensure sustainable growth and effective socio-economic management.
Perspective Planning Division Planning Commission Government of India July, 2004
Perspective Planning Division Planning Commission Government of India July, 2004
Keywords: Pension Liabilities; Central Government; Defined-Benefit Pension; Economic Sustainability; Pension Projections; Inflation Impact; Salary Expenditure; Fiscal Policy; Economic Reforms; Poverty; Capital Inflows; Debt Markets